Influence of the seismicity in Santiago de Cuba, geodynamics and the enviroment in the decisions of urban classification - Zapata-Balanqué, José; Del Pino-Boytel, Jorge; Domínguez, Rosalba; Yanetsy, Sandra (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2008)
The city of Santiago de Cuba and his (her, your) enviroment shaped by the basin that surrounds this one and his (her, your) bay has been determined by elements geomorfológicos, geodynamic and seismological that together with the antropismo product of the urban and insdutrial development of the city from the 16th century brings I obtain the degradation of the enviroment.  There are exposed the results of the map of seismic risk and of the monotoring of the geodynamic, hydrological and seismological variables that are realized in zones about the city of Santiago de Cuba for the clarification of the levels of interconnection of the seismicity moderated in the zone and the geodynamic existing phenomena and her influence on the urban environment.  They present problems that appear in the investment process, for the breach of the cycle of actions of research in the different stadiums of the same one on the part of the inverstors, to achieve a city sustentable.